2014
DOI: 10.1038/srep05882
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Graphitic Carbon Nitride for Metal-free, Flexible and Rewritable Nonvolatile Memory Device via Direct Laser-Writing

Abstract: Graphitic carbon nitride nanosheet (g-C3N4-NS) has layered structure similar with graphene nanosheet and presents unusual physicochemical properties due to the s-triazine fragments. But their electronic and electrochemical applications are limited by the relatively poor conductivity. The current work provides the first example that atomically thick g-C3N4-NSs are the ideal candidate as the active insulator layer with tunable conductivity for achieving the high performance memory devices with electrical bistabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 59 publications
(88 reference statements)
2
68
0
Order By: Relevance
“…Recently, Bojdys and coworkers presented a crystalline triazine-based graphitic carbon nitride with very low hydrogen content (0.51 wt%) and a carbon-tonitrogen ratio close to the theoretical one for g-C 3 N 4 [15]. Owing to their optoelectronic properties, these polymers have nonetheless found potential applications, from light-induced catalysis including hydrogen evolution from water [16,17] to chemical sensing [18,19] and electronic devices [15,20]. Advancement in these applications hinges on the detailed characterization of their physical properties, which so far have been limited due to difficulties in material processing.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, Bojdys and coworkers presented a crystalline triazine-based graphitic carbon nitride with very low hydrogen content (0.51 wt%) and a carbon-tonitrogen ratio close to the theoretical one for g-C 3 N 4 [15]. Owing to their optoelectronic properties, these polymers have nonetheless found potential applications, from light-induced catalysis including hydrogen evolution from water [16,17] to chemical sensing [18,19] and electronic devices [15,20]. Advancement in these applications hinges on the detailed characterization of their physical properties, which so far have been limited due to difficulties in material processing.…”
Section: Introductionmentioning
confidence: 94%
“…Simplistic architecture and fast switching characteristics have attracted their applications in neuromorphic computations, for example, mimicking synaptic functions by combining CMOS neurons and memristors in cross-bar configuration [15]. Organic and flexible memristors with the highest retention of 5 × 10 6 at the cost of low endurance, switching speeds, and lowtemperature range are demonstrated [16]- [18]. Kim et al [19] demonstrated Si-based inorganic memristors transferred onto organic substrate showing reasonably moderate parameters with a very low yield (60-85%) and higher operating voltage.…”
Section: B Memory Management Modulementioning
confidence: 99%
“…All-organic systems: integrating both devices and substrates made from organic materials or active materials devices inkjet (or screen-printed) on organic/paper substrates [38]- [42], and 2. Hybrid systems: combines the transfer of inorganic electronic devices onto flexible organic substrates using low-temperature direct deposition of inorganic on plastics using laser lift-off transfer or transfer printing techniques [18], [29], [43]- [46].…”
Section: A Organic and Hybrid Non-cmos Based Approachesmentioning
confidence: 99%
“…Nevertheless, the poor conductivity of g-C 3 N 4 is a serious problem strongly restricting the electron transportation and limiting the electrocatalytic activity [10]. Graphene, a two dimensional Л carbon structure material with unique electronic properties, large theoretical specific surface area and environmental benignity, has been recognized as a superior candidate for the construction of catalysts [11,12].…”
Section: Introductionmentioning
confidence: 99%